Bughat sebagai Jarimah Politik dalam Hukum Islam: Studi Konseptual serta Relevansi Konsep Bughat dalam Negara Modern - Lahmudinur; Muhammad Hilmi; Anida Kharamah; Raudah (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
This study examines the concept of bughat (rebellion) within Islamic law as a political crime that carries significant implications for social order and governance. Using a normative juridical approach, this research analyzes primary Islamic legal sources namely the Qur’an, hadith, and classical works of fiqh and fiqh siyasah as well as contemporary legal scholarship. Data are collected through an extensive literature review and analyzed using a descriptive-analytical method grounded in the framework of maqāṣid al-syarī‘ah. The findings show that bughat is defined by specific criteria, including the presence of an armed group possessing interpretive justification (ta’wil), organizational strength, and explicit opposition to legitimate authority. The study reveals that the sanctions for bughat prioritize conflict resolution, restoration of public security, and the prevention of broader social harm rather than punitive retaliation. Through the lens of maqāṣid al-syarī‘ah, the rules governing bughat emphasize the protection of life, the preservation of social stability, and the prevention of political corruption (dar’ al-mafāsid). The discussion further highlights the continued relevance of the bughat framework in contemporary contexts, particularly when aligned with procedural justice and international human rights principles. This study concludes that integrating classical Islamic jurisprudence with modern legal and ethical standards strengthens the applicability of bughat regulations in contemporary Muslim-majority legal systems.